Virtual teenage talk in game play: the nuances and variants in interactive written discourse - Chan, Swee Heng; Yong, Pui Li (Universiti Putra Malaysia Press, 2011)
In recent years, research in computer-mediated communication (CMC) via the Internet has revealed the fostering of a sense of community in which special, close, and intimate interactions can be traced. These research studies have employed both qualitative and quantitative approaches to get insights into the understudied virtual phenomenon. In an attempt to add to this body of knowledge, a study was conceptualized to analyse interactive written discourse (IWD) that takes place in game play. Game play attracts teenagers as participants and allows them to express themselves in virtual space that invites reciprocal exchange in a variety of contexts. These exchanges are subject to content and textual analysis to show the forms and performatives of language use in a specific sub-community of teenagers which invariably forms part of the larger community. The data give information about ‘virtual speak’ that helps to illuminate how and what teenagers talk about in virtual space through IWD. The results show specific themes of social interaction and particularities in language use that characterize the social dynamics of engagement in teenage game play.